Autoimmune Hemolytic Anemia After Inactivated Virus COVID-19 Vaccination: A Report of 2 Cases - Insiripong, Somchai; Anantasetagoon, Tanakorn; Sanglutong, Likhasit (Ramathibodi Medical Journal, 2022)
Very few cases of autoimmune hemolytic anemia (AIHA) have been reported after mRNA COVID-19 vaccinations. But herein we found 2 cases of AIHA after inactivated virus COVID-19 vaccination. Case 1: a 47-year-old Thai woman suffered from malaise, fatigue, and feverish feeling since the evening of the day of the first dose of inactivated virus COVID-19 vaccination (Sinopharm). She did not have any serious health problem prior this illness. Physical examination revealed marked pallor and body temperature was 38.1°C. Blood tests showed hemoglobin (Hb) 55 g/L, white blood cell (WBC) 12.2 × 109/L, platelet 310 × 109/L, nucleated red blood cell (RBC) 8/100 WBC, reticulocyte count 25.0%, direct antiglobulin test-4+ positive, indirect antiglobulin test-2+ positive. She was diagnosed with severe AIHA and well responsive to steroid therapy. Case 2: a 78-year-old Thai woman felt fatigue without fever 3 days after the second dose of inactivated virus COVID-19 vaccine (Sinopharm). Her underlying disease was anemia of the elderly with alpha thalassemia-1 heterozygosity. Her averaged Hb concentration before transfusion was 85 ± 3 g/L and she always needed transfusion every 2 months. Physical examination revealed only pallor. Blood test showed Hb 79 g/L, WBC 3.7 ×109/L, platelet 104 × 109/L, direct antiglobulin test-4+ positive, indirect antiglobulin test-4+ positive. She was diagnosed with AIHA and treated with cyclophosphamide and blood transfusion. Although the association between the inactivated virus COVID-19 vaccination and AIHA could not be simply concluded and the mix-and-match combination of different COVID-19 vaccines is promoted by Thai government, both of our patients chose to postpone the next dose of any kind of COVID-19 vaccine.